Environmental awareness and pro-environmental behavior: A case of university students in Malang city - Ramadhani Lausi Mkumbachi; I Komang Astina; Budi Handoyo (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2020)
University students exhibit low commitment towards pro-environmental behavior despite the facts that they know a lot about environmental issues. The objective of this study was (1) to know the level of environmental awareness and pro-environmental behavior and (2) to find relationship between environmental awareness and pro-environmental behavior among university students in Malang city. This study used descriptive quantitative research design using survey method. Data were collected using questionnaire instrument using a 3-point modified from Liker response scale. The results revealed that majority of the students possessed higher environmental awareness and exhibited high environmentally-friendly behavior. Likewise, there existed significant relationship between environmental awareness and pro-environmental behavior amongst university students in Malang city.Mahasiswa menunjukkan komitmen yang rendah terhadap perilaku prolingkungan meskipun mereka tahu banyak tentang masalah lingkungan. Tujuan dari penelitian ini adalah (1) untuk mengetahui tingkat kesadaran lingkungan dan perilaku pro-lingkungan dan (2) untuk menemukan hubungan antara kesadaran lingkungan dan perilaku pro-lingkungan di kalangan mahasiswa di Kota Malang. Penelitian ini menggunakan desain penelitian kuantitatif deskriptif dengan menggunakan metode survei. Data dikumpulkan dengan menggunakan instrumen kuesioner menggunakan 3 poin yang dimodifikasi dari skala respons Liker. Hasil penelitian menunjukkan bahwa mayoritas siswa memiliki kesadaran lingkungan yang lebih tinggi dan menunjukkan perilaku ramah lingkungan yang tinggi.